2012
DOI: 10.4049/jimmunol.1003944
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1 (CD90) Is an Interacting Partner for CD97 on Activated Endothelial Cells

Abstract: Leukocyte recruitment in response to inflammatory signals is governed, in part, by binding to Thy-1 (CD90) on activated endothelial cells (EC). In this study, we characterized the adhesion G-protein coupled receptor CD97, present on peripheral myeloid cells, as a novel interacting partner for Thy-1. CD97 was upregulated on polymorphonuclear cells (PMNC) of patients with psoriasis. In psoriatic skin lesions, CD97+ myeloid cells colocalized with Thy-1+ EC of small vessels in microabscesses, suggesting an interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 36 publications
(52 reference statements)
1
77
1
Order By: Relevance
“…A role of CD97 as receiver of local stromal and matrix adhesive codes would fit with its ability to engage with various ligands at low affinity. Besides CD55, CD97 binds the glycosaminoglycan dermatan sulfate, the integrin a5b1, and Thy-1/CD90 through different sites within the extracellular subunit (12,13,20). Similar characteristics have been reported for GPR56, an aGPCR expressed by neurons, various malignant cells, and cytotoxic lymphocytes (2,44).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…A role of CD97 as receiver of local stromal and matrix adhesive codes would fit with its ability to engage with various ligands at low affinity. Besides CD55, CD97 binds the glycosaminoglycan dermatan sulfate, the integrin a5b1, and Thy-1/CD90 through different sites within the extracellular subunit (12,13,20). Similar characteristics have been reported for GPR56, an aGPCR expressed by neurons, various malignant cells, and cytotoxic lymphocytes (2,44).…”
Section: Discussionmentioning
confidence: 50%
“…CD55 interacts with the N-terminal epidermal growth factor (EGF)-like domains of CD97 (6)(7)(8), an aGPCR broadly expressed by hematopoietic and nonhematopoietic cells (9)(10)(11). Subsequently identified aGPCR ligands were dermatan sulfate, a5b1 integrin, tissue transglutaminase 2, phosphatidylserine, LPS, C1q, lasso/teneurin-2, collagen III, and Thy-1/CD90 (12)(13)(14)(15)(16)(17)(18)(19)(20). Evidence was obtained that aGPCRs have a role in cell positioning and tissue organization in various organ systems (21,22); however, in the strictest sense, aGPCRs are still functional orphans.…”
mentioning
confidence: 99%
“…Several binding partners, including CD55 [37], chondroitin sulfate B [38], a5b1 and avb3 integrins [30], and Thy-1 (CD90) [39], which interact with different binding sites, have been identified for CD97. As similar phenotypes were seen in cells expressing CD97(EGF125) and CD97 (EGF1-5) isoforms, this suggests that CD55 and chondroitin sulfate B, which specifically bind the short and long CD97 isoforms, respectively, are probably not involved in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction has been extensively studied and shown to have a variety of effects on cell adhesion, cell motility, and carcinoma invasiveness but at present there is no evidence that this interaction can activate G protein-coupled signaling by CD97 (Mustafa et al, 2004;Liu et al, 2005). Moreover, the N terminus of GPR124 has been shown to facilitate adhesion by binding to both glycosaminoglycans and integrins (Vallon and Essler, 2006), and Thy-1 (CD90) has recently been shown to interact with CD97 to regulate polymorphonuclear cell adhesion (Wandel et al, 2012), but no corresponding signaling effects have been reported for these interactions.…”
Section: Importance Of the N Terminus For Adhesion Gpcr Signalingmentioning
confidence: 99%